2020
DOI: 10.1007/s00415-020-10087-z
|View full text |Cite
|
Sign up to set email alerts
|

Neurological manifestations in 404 COVID-19 patients in Washington State

Abstract: This hospital was among the first to report cases and deaths of COVID-19 patients in the United States. COVID-19 is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Most neurological manifestations of COVID-19 have been reported from non-USA health systems for hospitalized patients [1-3]. All patients had laboratory confirmed SARS-CoV-2 infection. Only new onset neurological manifestations were included. Study data were extracted from electronic medical records, and all neurological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 3 publications
5
32
1
Order By: Relevance
“…To date, five cohort studies provided a prevalence of neurological manifestations in a total of 2533 COVID-19 patients [2] , [3] , [4] , [5] , [6] ( Table 1 ). This prevalence ranged from 4.3 to 73.0% depending on which symptoms are considered.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, five cohort studies provided a prevalence of neurological manifestations in a total of 2533 COVID-19 patients [2] , [3] , [4] , [5] , [6] ( Table 1 ). This prevalence ranged from 4.3 to 73.0% depending on which symptoms are considered.…”
Section: Resultsmentioning
confidence: 99%
“…Impaired consciousness was one of the most common neurological symptoms in cohort studies, reported in 1.8 to 21.3% of hospitalized COVID-19 patients [2] , [3] , [4] , [5] , [6] ( Table 1 ), up to 69% in severe patients needing intensive care management [11] . Disorder of consciousness occurred with a mean time of onset of 8 to 9 days in the evolution of COVID-19, and was associated with severe infection, older age, higher creatine kinase levels, lower lymphocyte counts and higher blood urea nitrogen [2] , [3] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 45 patients discharged, 15 (33%) demonstrated a dysexecutive syndrome consisting of inattention, disorientation and/or poorly organized movements to command [4]. In a review of neurological manifestions in 404 hospitalized COVID-19 patients from the first US hospital with recorded cases, Agarwal et al [5] found neurological findings in 295 of 404 patients (73%). CNS symptoms were seen in 208 patients (52%) with altered mental status (21%) being the most common, followed by headache in 82 (20%), dizziness in 31 (8%), balance difficulties in 20 (5%), stroke in three (1%) and seizure in two.…”
Section: Introductionmentioning
confidence: 99%